Enhancing Student Learning in the Online Instructional Environment Through the Use of Universal Design for Learning - Kathleen A Boothe; Marla J Lohmann; Ruby Owiny (Networks: An Online Journal for Teacher Research, 2020)
As college faculty who prepare future teachers, we strive to teach our students through instruction and modeling best practices in teaching. We constantly evaluate our teaching and make adjustments to include updated knowledge about effective instruction. The evaluation and adjustments made to our courses lend themselves to action research. We take what we learn from our research and make appropriate changes to better meet the diverse needs of students. This article provides an overview of a final project that used Universal Design for Learning (UDL) for assessing student knowledge. This research focused on the principle of Multiple Means of Action and Expression and the impact the UDL final project had on student learning as well as overall perceptions of the project. Results indicate that participants enjoyed the final project and that it impacted their learning. Students reported enjoying having choice in how they demonstrated their understanding of the content.
Keywords: action research; college teaching; online learning; teacher preparation; Universal Design for Learning